Uniform α-Fe2O3 nanoparticles with narrow gap immobilized on CNTs through N-doped carbon as high-performance lithium-ion batteries anode. Issue 11 (1st June 2021) - Guo, Jinze; Wang, Shuhui; Sun, Xiaohong; Guo, Ruisong; Xiong, Kunzhou; Ling, Rui; Shen, Kaier; Cui, Jiahao; Ma, Hongyun; Zhou, Jiang; Cai, Shu; Sun, Jiefang
Abstract: Fe2 O3 with high theoretical capacity, low cost, and environmental friendliness has been attracted great attention in lithium-ion batteries (LIBs), which however is limited by low rate capability and fast capacity fading owing to low electronic conductivity, self-aggregation, and sever volume expansion. CNTs with excellent conductivity and unique 3D interconnected network are ideal matrices for composite electrochemical materials, but it is difficult to meet the demand of high capacity. Here, uniform α-Fe2 O3 nanoparticles with narrow gap (~1.4 nm) were immobilized on CNTs through N-doped carbon (α-Fe2 O3 /CNTs-NC) that can address these issues. As an advanced LIBs anode, the electrode displays unprecedented specific capacity (1173 mAh/g at 0.2 A/g) and outstanding rate behavior (716.4 mAh/g at 5.0 A/g after 1200 cycles), which are even superior to the theoretical capacity (1007 mAh/g) and the performance of most reported Fe2 O3 -based anodes. Homogeneous nano-sized α-Fe2 O3 with a narrow gap highly shortens the diffusion path for Li + transport, exposes quite sufficient active sites, and prevents the volume change. Moreover, the 3D backbone of CNTs with a more homogeneously distributed electric field can enhance conductivity, and tightly contact with α-Fe2 O3 by NC, then obtain robust structural stability, which boosts LIBs in storage capacity, rate capability, and cycling stability.